Investigating the Low Motivation of Young Couples for Childbearing in Shiraz Through Developing a Conceptual Model Using a Quantitative Approach - Fakhar, Maryam; Sohrabi Shekefti, Nadereh; Samani, Siamak (Applied Family Therapy Journal (AFTJ), 2025)
Objective: Considering the significance of population and its optimal growth in Iran, the present study examined the low motivation of young couples for childbearing in Shiraz by developing a conceptual model using a quantitative approach. Methods: This research is applied in terms of its goal. The statistical population of this study includes all young couples without children in Shiraz in 2021 (based on the 2016 census, approximately 14% of couples are childless). According to the population size, the number of questions, Cochran’s formula, and the G-power sample adequacy index, the approximate sample size consisted of 300 young childless couples, who were selected using the convenience sampling method. Data were collected using a researcher-made questionnaire, and based on factor analysis, the conceptual model of factors was explained and extracted. To test the model, the structural equation modeling approach was employed. The software used in this research was SPSS and AMOS. Findings: The results showed significant differences between the component of economic support and the components of personal growth inhibition, body self-concept, semantic attitude, communicative attitude, and social judgment. According to the model’s fit indices, it was observed that the X2/df index was equal to 3.70, which is at an acceptable level. Additionally, the values of the RMSEA index were 0.08, CFI was 0.843, FMIN was 3.21, NFI was 0.798, ECVI was 3.70, and IFI was 0.844, all of which were at an appropriate level. Therefore, the model had a good fit. Conclusion: Based on the research findings, it is recommended that researchers focus on improving attitudes in the areas of body self-concept, social judgment, semantic attitude, and communicative attitudes regarding childbearing.